Results of Four-Stented Biological Aortic Valves and How They Compare to PARTNER-3 - Rashvand, Jacqueline; Ostovar, Roya; Schroeter, Filip; Hartrumpf, Martin; Kuehnel, Ralf-Uwe; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2022)
Objective According to our nationwide registry, total numbers of surgical aortic valve implantation (sAVR) are constantly declining, while transcathether aortic valve implantation (TAVI) indications are widened toward intermediate- and low-risk patients. So, is there still room for conventionally implanted valves? Can results compete with TAVI or will sAVR be marginalized in the near future?Methods Between 2011 and 2019, 1,034 patients (67.1% male, mean = 72.2 years) were enrolled receiving stented biological valves with or without concomitant coronary artery bypass grafting (CABG), atrial ablation, or wrapping of the ascending aorta. Odds ratios for the early and late mortality were calculated regarding comorbidities as potential risk factors. Statistical analysis was performed using SPSS.Results Overall, early mortality (EM) was 6.1%, 1-year mortality was 11.2%, and 5-year mortality was 19.9%. In low-risk patients (EuroSCORE II <4%), it was 1.0, 2.7, and 9.3%. Incidence of EM was significantly increased following decompensation, prosthetic valve, pacemaker carrier, dialysis, and pulmonary hypertension. Postoperative complications, such as systemic inflammatory response syndrome (SIRS), sepsis, multiorgan failure, hepatic failure, dialysis, gastrointestinal bleeding, and ileus, also increased EM. Late mortality was significantly increased by dialysis, hepatic cirrhosis, infected port system, aortic valve endocarditis, prosthetic valve carrier, and chronic hemodialysis.Conclusion Conventionally implanted aortic valves do well early and late. The fate of the patient is dependent on individual risk-factors. Particularly, in low-risk patients, sAVR can compete with TAVI showing overall good early, as well as late results being even superior in some important aspects such as pacemaker implantation rate. Thus, the time is yet not ripe for TAVI to take over primary indications for AVR in low-risk patient.
Keywords: aortic valve and root; outcomes; heart valve surgery